The Effect of Literacy Level on Students’ Learning Achievement In Entrepreneurship Subject In SMK Sultan Fatah Demak - Iin Yuliasanti; Marhaeni Dwi Satyarini (Universitas Ivet, 2020)
Abstrak UNESCO menyebutkan hanya 0,001% penduduk Indonesia yang memiliki tingkat literasi tinggi. Untuk meningkatkan kemampuan literasi siswa, SMK Sultan Fattah Demak memiliki program literasi yang memberi kesempatan siswa untuk membaca 15 menit sebelum pembelajaran dimulai pada setiap tanggal 17. Penelitian ini bertujuan untuk mengetahui tingkat literasi, prestasi dan pengaruh tingkat literasi terhadap prestasi belajar siswa pada mata pelajaran Kewirausahaan, di SMK. Sultan Fatah Demak. Populasi penelitian siswa kelas XI sebanyak 217 siswa, dan sampel sejumlah 135 siswa. Variabel penelitian adalah : tingkat literasi siswa sebagai variable independent, dan prestasi belajar mata pelajaran Kewirausahaan sebagai variable dependent. Hipotesis penelitian : ada pengaruh tingkat literasi terhadap prestasi belajar siswa pada mata pelajaran Kewirausahaan. Pengumpulan data menggunakan metode angket, wawancara, observasi dan dokumentasi, data terkumpul dianalisis dengan teknik regresi linier. Hasil penelitian menunjukkan: 1). Tingkat literasi siswa yang menjadi responden menunjukkan nilai rerata 76.95% berada pada kategori tinggi, 2). Prestasi belajar siswa berdasarkan nilai raport semester gasal, menunjukkan nilai minimal 80 dan nilai maksimal 92, dengan nilai rerata 85,4 dengan kategori tuntas. 3). Hasil analisis regresi dengan uji anova diperoleh persamaan regresi Y = 51,4 + 0.276X, nilai F = 1151,72 dengan signifikansi 0,00, artinya: hipotesis penelitian yang menyatakan ada pengaruh signifikan tingkat literasi terhadap prestasi belajar siswa diterima. Abstract UNESCO claimed that there was only 0.001% Indonesian who possessed high literacy level. In this regard to improve students’ literacy skills, SMK Sultan Fatah Demak owns literacy program that provides students opportunity to read for 15 minutes before the class begins in the 17th date each month. This study has its purpose to reveal literacy level, achievement, and literacy effect on students’ learning achievement in Entrepreneurship subject in SMK Sultan Fatah Demak. The population of this study covers grade XI students as many as 217 and the sample consists of 135 students. The variable of this study is students’ literacy level as the independent variable and learning achievement in Entrepreneurship subject as the dependent variable. The hypothesis of this study states there has been found significant effect of literacy level on students’ learning achievement in Entrepreneurship subject. The data collection uses questionnaire, interview, observation, and documentation method. The collected data is analyzed with linear regression technique. The research results show 1). Students’ literacy level being the respondent shows average scores 76.95 which is considered to be high in category, 2). Students’ learning achievement as shown in the odd semester report book shows minimum score 80 and maximal score 92 that constitutes 85.4 in average, and it categorized to be completed, 3). Regression analysis results with anova test resulted in regression equation Y = 51.4 + 0.276 X, F score = 1151.72 with significance 0.00 that means hypothesis explaining it is found to be significant effect of literacy level on students’ learning achievement is accepted. Keywords: Analysis, Online Learning, Covid-19 Pandemic Period